Changing Nordic model? A policy analysis - Heikki Palviainen (University of Essex, Institute for Social and Economic Research (ISER), 2019)
Based on simulated counterfactual analyses, this paper studies the long-term evolution of key policy outcomes associated with the Nordic model. The results show that Finland had the most redistributive policy changes in the studied time periods. The Danish flexicurity model involves high benefit levels, and the participation tax rates were the highest. The Swedish work-line policy increased the risk of poverty by 1.0 percentage point and the Gini coefficient by 0.4. In Sweden, the behavioural effects did not fully offset the negative static effects on the risk-of-poverty rate and inequality. From a policy perspective, the results indicate that the Nordic model is resilient. In Sweden, a significant increase in the risk of poverty implies that there are other factors, such as immigration, that challenge the Nordic model.
Keywords: H23; I32; I38; 330; welfare states; Nordic countries; social protection; poverty; microsimulation